Soil water retention and s index after crop rotation and chiseling - Calonego, Juliano Carlos [UNESP] (2011)
Soil compaction can be minimized either mechanically or biologically, using plant species with vigorous root systems. An experiment was carried out with soybean (Glycine max) in rotation with triticale (X Triticosecale) and sunflower (Helianthus annuus) in fall-winter associated with pearl millet (Pennisetum glaucum), grain sorghum (Sorghum bicolor) or sunn hemp (Crotalaria juncea) in spring. Crop rotation under no-till was compared with mechanical chiseling. The experiment was carried out in Botucatu, São Paulo State, Brazil. Soil quality was estimated using the S index and soil water retention curves (in the layers of 0-0.05, 0.075-0.125, 0.15-0.20, 0.275-0.325, and 0.475-0.525 m deep). Crop rotation and chiseling improved soil quality, increasing the S index to over 0.035 to a depth of 20 cm in the soil profile. The improved soil quality, as shown by the S index, makes the use of mechanical chiseling unnecessary, since after 3 years the soil physical quality under no-tilled crop rotation and chiseling was similar.